(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
This review deals with aspects to consider concerning intelligent polymer coatings. The expression "intelligent polymer coatings" alludes to the concept of coatings being able to sense their environment and properly react to that stimulus. Great efforts have been made to create a novel versatile coating capable of detecting corrosion, pressure, and temperature. The discussion focused on the extent and restrictions of self-healing principles in polymer coatings. Additionally, we discuss the outline of present methodologies and technologies that cover the zones of low molecular weight antibacterial agents and antibacterial polymer coatings. The concentration and spectrum distribution of the optical source can be regulated by employing optical components and filtering optical projection systems that incorporate filters, mirrors, lenses, and optical fibers.